(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Supracondylar Fractures of the Distal Humerus are the most common elbow fractures seen in children and the most common fracture requiring surgery in children, is reported to occur in 65.45% of patients with upper limb fractures in children according to Boyd and Altenberg. Objective: Evaluate the treatment results of supracondylar fractures of the distal humerus in children by Percutaneous Pinning under fluoroscopy at Ba Ria Hospital. Research subjects and methods: Cross-sectional descriptive study, patients with grade II and III Supracondylar Fractures of the Distal Humerus according to the Gartland-Wilkins classification, were operated on in 2014. Results: The peak age for supracondylar fractures is 3 - 6 years old approximately 52.9%, of male children (67.6%), the left hand is more than 1.42 times than the right hand. The main cause is living accidents (85.3%). Baumann angle under 6o withdraw needle and pinning (accounting for 85.3%), with no secondary rotational displacement after needle removal. The bulbar body angle was assessed at a good (82.4%). According to Flynn, the recovery of elbow flexion and extension range of motion is good (82.4%). There was no ulnar nerve injury after pinning . Conclusion: The cross-needle method through the skin to treat fractures on both condyles is a fairly solid and safe fixation method with few complications.